2012
DOI: 10.1186/1740-3391-10-5
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal-and sex-related difference of metallothionein expression in mice

Abstract: BackgroundMetallothionein (MT) is a small, cysteine-rich, metal-binding protein that plays an important role in protecting against toxicity of heavy metal and chemicals. This study was aimed to define diurnal and sex variation of MT in mice.MethodsAdult mice were maintained in light- and temperature-controlled facilities for 2 weeks with light on at 8:00 and light off at 20:00. The blood, liver, and kidneys were collected every 4 h during the 24 h period. Total RNA was isolated, purified, and subjected to real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
2
18
1
Order By: Relevance
“…Cry1 showed a 13-fold difference between nadir and peak in females and 23-fold in males. There was basically no sex difference in circadian variation of Cry1, except for slightly higher expression in males at 22:00 h. For the antiphase clock gene Bmal1, there was a 14-fold difference in females and 54-fold in males, and females had higher mRNA levels than males at 10:00 and 2:00 h. We have examined the expression of six clock genes in our recent publications (Xu et al, 2012; Zhang et al, 2009, 2011, 2012), and the oscillation patterns observed in C57 mice are similar in KM mice and represent typical circadian rhythms, thus validating further analysis of the Cyp genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cry1 showed a 13-fold difference between nadir and peak in females and 23-fold in males. There was basically no sex difference in circadian variation of Cry1, except for slightly higher expression in males at 22:00 h. For the antiphase clock gene Bmal1, there was a 14-fold difference in females and 54-fold in males, and females had higher mRNA levels than males at 10:00 and 2:00 h. We have examined the expression of six clock genes in our recent publications (Xu et al, 2012; Zhang et al, 2009, 2011, 2012), and the oscillation patterns observed in C57 mice are similar in KM mice and represent typical circadian rhythms, thus validating further analysis of the Cyp genes.…”
Section: Resultsmentioning
confidence: 99%
“…Special analysis of circadian rhythms followed the method of Refinetti et al (2007), as described in our recent publications (Xu et al, 2012; Zhang et al, 2012). Sex difference at the same time point was analyzed by Student’s t test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diurnal variation of hepatic detoxification enzyme genes. Many antioxidant enzyme genes display diurnal variations, such as the Nrf2 detoxication pathway genes [30], enzymatic detoxication components such as superoxide dismutase (SOD), catalase, glutathione peroxidase (GSH-Px1) and non-enzymatic protein such as metallothionein (MT) [31]. GSH is low in the afternoon which is partially responsible for acetaminophen hepatotoxicity when given in the afternoon [23].…”
Section: Diurnal Variation Of Hepatic Uptake Transportersmentioning
confidence: 99%
“…In the liver this is functionally important and may explain the decreased acetaminophen hepatotoxicity during the light/sleep phase [190]. Interestingly, hepatic metallothionein levels peak at the beginning of the active period, which may afford some level of enhanced antioxidant defense at this time [191]. …”
Section: Integration Of Mitochondrial Function Autophagy and Circmentioning
confidence: 99%